2021
DOI: 10.1177/15347346211029078
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Bone Marrow Cells Preactivated With Sodium Nitroprusside Improves Acute Wound Healing in Rabbits

Abstract: The development of wound healing impairment mainly represents challenging clinical problems. The less and high concentrations of nitric oxide can influence angiogenesis, remodeling, and proliferation of skin cells. Delayed acute wounds generally have failed to progress via the normal stages of healing. Such wounds usually enter a state of pathological inflammation due to a postponed, incomplete, and uncoordinated healing process. This study aimed to investigate the effect of normal bone marrow cells (BMCs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Growth factors are dependable for mobilizing, stimulating, and activating of SCs from the BM. In our previous study, the regeneration of specific tissue in that area depends on the specific growth factor and optimum doses of NaNP with BMCs that enhance WH [26]. So the SC research tells about the proper sequence of growth factors i. e. needed for specific tissue regeneration [39].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Growth factors are dependable for mobilizing, stimulating, and activating of SCs from the BM. In our previous study, the regeneration of specific tissue in that area depends on the specific growth factor and optimum doses of NaNP with BMCs that enhance WH [26]. So the SC research tells about the proper sequence of growth factors i. e. needed for specific tissue regeneration [39].…”
Section: Discussionmentioning
confidence: 98%
“…Pretreatment of b.M cells Added NaNP as an induction factor to BMCs suspension for the increase of differentiation potential of a cell, about 50 µL & 100 µL from the stock solution [26].…”
Section: Wound Healing Percentage In Nth Day= × 100mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that BM-derived stem cells may be involved in the acceleration of wound healing ( Wu et al ., 2007 ) including burn injury ( Xue et al ., 2013 ). It was recently reported also that transplantation of BM cells pre-activated with sodium nitroprusside enhances acute wound curing in rabbits ( Fatima and Saleem, 2023 ). Parelle, enhancement of chronic wound curing by pre-activated BM cells with sodium nitroprusside in rabbits has been reported ( Fatima et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium nitroprusside has a wide range of pharmaceutical applications. Because of its ability to release NO, sodium nitroprusside can dilate blood vessels and regulate wound healing [11]. In recent years, AgNP NPs have shown potential for medical applications due to their excellent physicochemical properties, antimicrobial properties, and biocompatibility [12].…”
Section: Introductionmentioning
confidence: 99%